Inflation Targeting : A Fossil-Fuel-Driven Supply-Side Shock Effect on Inflation and Inflation Expectations - Nasenko, Nikolaj; Šíma, Ondřej; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
A fossil-fuel-driven supply-side shock has the potential for a serious and widespread effect on inflation. The historical and the most recent events provide us with great evidence. Fossil fuel market drivers are a notable example of events that are beyond the control of inflation-targeting central banks. The threat of unanchoring inflation expectations may under such circumstances be of special concern. In this regard, this thesis examines what is the appropriate monetary policy response from theoretical and practical perspectives. The most recent energy shock of 2021–2022 in the context of the Czech economy and the CNB’s monetary policy reaction was of primary interest. Our analysis suggests that the CNB Bank Board’s decision to initiate monetary tightening was required due to both, strong demand and the risk of second-round effects over the monetary policy horizon. According to our findings, dampening the aggregate demand may have suppressed incentives for further price increases and may have avoided prolonging the highly inflationary period. In addition, we find evidence that suppressing second-round effects, in particular the wage-price spiral, through changes in the policy rate (ceteris paribus) is rather ineffective.
Vedoucí práce: Ondřej Šíma
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses